Die Medizininformatik-Initiative im Überblick – Aufbau einer Gesundheitsforschungsdateninfrastruktur in Deutschland - Semler, Sebastian C.; Boeker, Martin; Eils, Roland; Krefting, Dagmar; Loeffler, Markus; Bussmann, Jens; Wissing, Frank; Prokosch, Hans-Ulrich (Bundesgesundheitsblatt, Gesundheitsforschung, Gesundheitsschutz, 2024)
The Medical Informatics Initiative (MII) funded by the Federal Ministry of Education and Research (BMBF) 2016–2027 is successfully laying the foundations for data-based medicine in Germany. As part of this funding, 51 new professorships, 21 junior research groups, and various new degree programs have been established to strengthen teaching, training, and continuing education in the field of medical informatics and to improve expertise in medical data sciences. A joint decentralized federated research data infrastructure encompassing the entire university medical center and its partners was created in the form of data integration centers (DIC) at all locations and the German Portal for Medical Research Data (FDPG) as a central access point. A modular core dataset (KDS) was defined and implemented for the secondary use of patient treatment data with consistent use of international standards (e.g., FHIR, SNOMED CT, and LOINC). An officially approved nationwide broad consent was introduced as the legal basis. The first data exports and data use projects have been carried out, embedded in an overarching usage policy and standardized contractual regulations. The further development of the MII health research data infrastructures within the cooperative framework of the Network of University Medicine (NUM) offers an excellent starting point for a German contribution to the upcoming European Health Data Space (EHDS), which opens opportunities for Germany as a medical research location.
CRIS-Team Scopus Importer:2024-06-14
Keywords: Data use and access; Medical informatics; Research data infrastructure; Secondary use of health data; Standardization